Beyond capacity limits: can social cohesion offset the impact of service constraints on youth mental health? - Jo-An Occhipinti; Nicholas Ho; Paul Crosland; Sam Huntley; Wendy Hawkins; Adam Connell; Judith Piccone; Sarah Piper; Seyed Hossein Hosseini; Catherine Vacher; Jordan van Rosmalen; Sophie Morson; et al. (European Psychiatry)
Abstract Background Rates of youth anxiety, depression, and self-harm have increased substantially in recent years. Expansion of clinical service capacity is constrained by workforce shortages and system fragmentation, and even substantial investment may not achieve the scale of growth required to address unmet need. Preventive strategies – such as strengthening social cohesion – are therefore essential to alleviate mounting pressures on the mental health system, yet their potential to compensate for these constraints remains unquantified.